High-strength corrosion-resistant puncture-resistant fiber composite material and preparation method thereof
By anchoring the nuclear shell SI3N4@ZIF-8 structural material on the high-performance fiber and modified the interface, the high-intensity corrosion resistance resistance fiber composite materials are prepared, which solves the weight of existing spiny materials and insufficient acid and alkali resistance. The problem realizes protective materials for light and high -intensity and multiple functions.
Patent Information
- Application Number
- CN202411663387.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-28
AI Technical Summary
Existing puncture-resistant materials are difficult to reduce weight while maintaining puncture resistance and are difficult to resist acid-base erosion in extreme environments.
The nuclear shell SI3N4@ZIF-8 structural material is anchored on the surface of high-performance fibers, and the interface is modified through the polymer/polymer coating solution to prepare a high-strength corrosion resistance and anti-puncture fiber composite material.
It realizes the resistance and corrosion resistance of materials without increasing weight, and is suitable for protective equipment for high -risk environments.
Smart Images

Figure CN119371693A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fiber composite materials, and in particular to a high-strength, corrosion-resistant and puncture-resistant fiber composite material and a preparation method thereof. Background Art
[0002] At present, bulletproof and stab-proof equipment is not only widely used in the military field, but its importance has also expanded to the civilian field, including public safety, special police operations, high-risk industries, medical practice and sports protection. Although traditional stab-proof materials, such as steel plates, ceramics, aluminum alloys and titanium alloys, have certain protective effects, there is an obvious trade-off between their protective performance, weight and flexibility, which limits their widespread use in practical applications.
[0003] With the continuous advancement of high-performance fiber technology, some fabrics with high modulus, high strength and low density, such as ultra-high molecular weight polyethylene and aramid fabrics, have been widely used in the field of flexible puncture-resistant materials due to their excellent flexibility and puncture resistance. However, the single-layer structure of these high-performance fabrics is difficult to provide sufficient puncture protection. Although the stacking of multiple layers of fabrics can enhance the protective performance, it often leads to increased weight and reduced flexibility. Therefore, the main challenge at present is how to reduce the weight of the material while maintaining puncture resistance. In addition, for police, firefighters and industrial workers working in extreme environments, soft protective equipment with puncture resistance and acid and alkali resistance is also crucial. The various dangerous and high-risk environments faced by these industries require protective materials to effectively resist acid and alkali corrosion.
[0004] Silicon nitride zeolite imidazole core-shell structure material (Si3N4@ZIF-8) is a nanoscale ordered assembly structure material, whose core-shell structure can be connected to each other by chemical bonds or physical forces to form a well-defined composite material. This material has shown significant advantages in the field of puncture protection, mainly in the following aspects: the introduction of Si3N4@ZIF-8 can improve the strength and toughness of the composite material, and its unique framework structure can effectively disperse and buffer the external force, enhancing the material's puncture resistance; Si3N4@ZIF-8 has good thermal stability and chemical stability, which can enhance the stability of the material in extreme environments and extend its service life; after the introduction of Si3N4@ZIF-8 in the composite material, the puncture resistance can be improved by increasing the hardness and tensile strength of the material, and its unique pore structure can also provide additional blocking effect; Si3N4@ZIF-8 is relatively lightweight, which can reduce the weight of the overall material without sacrificing puncture resistance, which is particularly important for applications that require lightweight and high-strength materials (such as protective clothing). In general, Si3N4@ZIF-8, as an excellent nanoscale ordered assembly structural material, has broad application prospects in puncture-resistant fibers. Summary of the invention
[0005] The purpose of the present invention is to provide a high-strength corrosion-resistant and puncture-resistant fiber composite material and a preparation method thereof in order to solve the above problems. The material prepared by the present invention not only has excellent corrosion resistance, but also has excellent puncture resistance. This composite material is designed to meet the needs of modern high-performance protective equipment and has broad application potential and market prospects.
[0006] The present invention achieves the above-mentioned purpose through the following technical solutions:
[0007] A method for preparing a high-strength, corrosion-resistant and puncture-resistant fiber composite material comprises the following steps:
[0008] S1. Preparation of active high-performance fibers: cleaning and drying the surface of the high-performance fibers, and then placing the fibers in a plasma reaction chamber for plasma treatment, thereby obtaining active high-performance fibers;
[0009] S2, preparing core-shell Si3N4@ZIF-8 dispersion: dissolving nano-Si3N4, zinc salt and 2-methylimidazole in a sufficient amount of alcohol solvent, and preparing core-shell Si3N4@ZIF-8 crystal dispersion by microwave-ultrasound assisted method;
[0010] S3, preparation of Si3N4@ZIF-8 modified fibers: anchoring the core-shell Si3N4@ZIF-8 crystals on the surface of the active high-performance fiber obtained in S1 by using the core-shell Si3N4@ZIF-8 dispersion obtained in S2 through a surface deposition process to obtain Si3N4@ZIF-8 modified fibers;
[0011] S4, preparation of high-performance fiber composite materials: using polymer / polymer coating solution to perform interface modification on the Si3N4@ZIF-8 modified fiber obtained in S3 to prepare high-performance fiber composite materials;
[0012] S5. Preparation of high-strength, corrosion-resistant and puncture-resistant fiber composite materials: The high-performance fiber composite materials obtained in S4 are laminated and compounded to finally prepare high-strength, corrosion-resistant and puncture-resistant fiber composite materials.
[0013] According to a further embodiment, the high-performance fiber in step S1 is at least one of ultra-high molecular weight polyethylene fiber, aramid fiber, polysulfone fiber, nylon fiber, carbon fiber, polyimide fiber, and polyester fiber;
[0014] According to a further solution, the gas used in the plasma treatment technology in step S1 is at least one of oxygen, nitrogen, hydrogen, argon and helium, the treatment time is 0.5-10 min, the treatment pressure is 10-130 Pa, the treatment temperature is 20-60° C., and the treatment power is 20-300 W;
[0015] According to a further scheme, the zinc salt in step S2 is at least one of zinc acetate, zinc chloride, zinc nitrate, zinc sulfate, zinc acetate, zinc phosphate, and zinc carbonate, the concentration of the zinc salt solution is 0.01-0.5 mol / L, the treatment time of the microwave-ultrasound-assisted method is 1-48 h, the treatment temperature is 20-200° C., and the mass ratio of nano-Si3N4, 2-methylimidazole, and zinc salt in the core-shell Si3N4@ZIF-8 dispersion is 1:2-3:0.7-0.9;
[0016] A further solution is that the alcohol solvent in step S2 is at least one of methanol, ethanol, benzyl alcohol, ethylene glycol, propylene glycol, n-butanol, and cyclohexanehexol, and the average particle size of the core-shell Si3N4@ZIF-8 crystal is 3.0 μm to 4.0 μm;
[0017] According to a further embodiment, the surface deposition process in step S3 is at least one of an ultrasonic assisted method, a heat treatment method (solvent evaporation, heating crystallization, etc.), a covalent bonding method, a chemical deposition method, and an electrochemical deposition method;
[0018] According to a further embodiment, the polymer in step S4 is at least one of polyethylene terephthalate (PET), polyurethane (PU), polyvinyl chloride (PVC), polypropylene (PP), polyethylene (PE), polycarbonate (PC), polyamide (PA), polyester elastomer (TPEE), polyetheretherketone (PEEK), ethylene-vinyl acetate copolymer (EVA), polyvinylidene fluoride (PVDF), and polytetrafluoroethylene (PTFE);
[0019] According to a further embodiment, the polymer coating solution in step S4 is a mixture of a polymer and an organic / inorganic solvent or a mixed coating solution formed by a resin and an inorganic powder;
[0020] According to a further embodiment, the process of interface modification in step S4 is one or more of hot pressing, dipping, coating, spraying, roller coating, roller pressing, casting, and ultrasonic vibration treatment;
[0021] According to a further solution, the number of laminated layers in step S5 is 2 to 40, wherein the limiting oxygen index of two layers is 20-45%, the maximum puncture force is 350-550N, and the tensile strength is 450-820MPa.
[0022] Another aspect of the present invention also provides a high-strength, corrosion-resistant and puncture-resistant fiber composite material obtained by the above-mentioned preparation method and its use.
[0023] The beneficial effects of the present invention are:
[0024] A high-strength, corrosion-resistant and puncture-resistant fiber composite material and a preparation method thereof of the present invention firstly treat the high-performance fiber with plasma, which can change the chemical composition and structure of the fiber surface, increase the surface functional groups (such as hydroxyl and carboxyl groups), and thus enhance the binding ability of the fiber with other materials (including coatings, adhesives and dyes). Then, the core-shell Si3N4@ZIF-8 crystals are anchored to the surface of the high-performance fiber treated with plasma by a surface deposition process. The presence of Si3N4@ZIF-8 can optimize the absorption and dispersion of energy during the puncture process, and significantly improve the puncture resistance and mechanical properties of the material. In addition, by using a polymer / polymer coating solution to modify the fabric interface, not only the durability and wear resistance of the fabric are enhanced, but also the fabric is endowed with special functions such as corrosion resistance, antibacterial and antistatic, so that it can better resist the influence of the external environment. Finally, by stacking and compounding the obtained fiber material, the puncture protection level of the material is further improved, thereby developing a high-performance protective material with multiple advantages such as corrosion resistance and puncture resistance, providing a new solution for modern high-performance protective equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0026] Figure 1 The present invention is a flow chart of the preparation method.
[0027] Figure 2 This is a scanning electron microscope image of the Si3N4@ZIF-8 modified aramid fiber obtained in Example 1 of the present invention.
[0028] Figure 3 This is a scanning electron microscope image of the Si3N4@ZIF-8 modified ultra-high molecular weight polyethylene fiber obtained in Example 3 of the present invention. DETAILED DESCRIPTION
[0029] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.
[0030] Example 1
[0031] A high-strength corrosion-resistant and puncture-resistant fiber composite material and a preparation method thereof, comprising the following steps:
[0032] S11, preparing active high-performance fibers: using a soft brush to gently scrub the surface of the aramid fiber to remove dust and dirt, and then placing it in a plasma reaction chamber for plasma treatment (the gas selected is hydrogen, the treatment time is 10 min, the treatment pressure is 50 Pa, the treatment temperature is 40° C., and the treatment power is 50 W) to obtain active high-performance fibers;
[0033] S12, preparing core-shell Si3N4@ZIF-8 dispersion: 78.43 g of nano-Si3N4, 175.93 g of 2-methylimidazole, and 63.59 g of zinc chloride were dissolved in 1000 mL of methanol, and a core-shell Si3N4@ZIF-8 dispersion was prepared by a microwave-ultrasound-assisted method (treatment time 1 h, temperature 200°C);
[0034] S13, preparation of Si3N4@ZIF-8 modified fibers: immerse the active high-performance fibers obtained in S11 in the core-shell Si3N4@ZIF-8 dispersion obtained in S12, anchor the core-shell Si3N4@ZIF-8 crystals on the fiber surface by ultrasonic-assisted method (ultrasonic treatment time 8h), and prepare Si3N4@ZIF-8 modified fibers;
[0035] S14, preparation of high-performance fiber composite materials: PET (10g / m 2 ) The surface of Si3N4@ZIF-8 modified fiber obtained by S13 was subjected to interface modification by hot pressing on a flat hot press (hot pressing temperature was 200°C, hot pressing pressure was 5 MPa, and hot pressing time was 5 min) to prepare a high-performance aramid fiber composite material;
[0036] S15. Preparation of high-strength, corrosion-resistant and puncture-resistant fiber composite materials: Take two layers of the high-performance aramid fiber composite material obtained in S14 and stack and compound them to prepare a high-strength, corrosion-resistant and puncture-resistant fiber composite material.
[0037] Example 2
[0038] A high-strength corrosion-resistant and puncture-resistant fiber composite material and a preparation method thereof, comprising the following steps:
[0039] S21, preparing active high-performance fiber: using organic solvent acetone to clean the surface of aramid fiber, and placing it in a plasma reaction chamber for plasma treatment after drying (gas selected is oxygen, treatment time is 5 min, treatment pressure is 20 Pa, treatment temperature is 30° C., treatment power is 20 W) to obtain active high-performance fiber;
[0040] S22, preparing core-shell Si3N4@ZIF-8 dispersion: 83.47 g of nano-Si3N4, 187.25 g of 2-methylimidazole, and 67.68 g of zinc acetate were dissolved in 1000 mL of benzyl alcohol, and a core-shell Si3N4@ZIF-8 dispersion was prepared by a microwave-ultrasound-assisted method (treatment time 3 h, temperature 150° C.);
[0041] S23, preparation of Si3N4@ZIF-8 modified fibers: immerse the active high-performance fibers obtained in S21 in the core-shell Si3N4@ZIF-8 dispersion obtained in S22, anchor the core-shell Si3N4@ZIF-8 crystals on the fiber surface by solvent evaporation method (treatment time 8h, treatment temperature 50°C), and prepare Si3N4@ZIF-8 modified fibers;
[0042] S24, preparation of high-performance fiber composite materials: take PVC (5g / m 2 ) The Si3N4@ZIF-8 modified fiber surface obtained by hot pressing on S23 was modified by a flat hot press (hot pressing temperature was 200°C, hot pressing pressure was 5 MPa, hot pressing time was 5 min) to perform interface modification to prepare a high-performance aramid fiber composite material;
[0043] S25. Preparation of high-strength, corrosion-resistant and puncture-resistant fiber composite materials: Take two layers of the high-performance aramid fiber composite material obtained in S24 and stack and compound them to prepare a high-strength, corrosion-resistant and puncture-resistant fiber composite material.
[0044] Example 3
[0045] A high-strength corrosion-resistant and puncture-resistant fiber composite material and a preparation method thereof, comprising the following steps:
[0046] S31, preparing active high-performance fibers: using a soft brush to gently scrub the surface of the ultra-high molecular weight polyethylene fiber, and then placing it in a plasma reaction chamber for plasma treatment (the gas selected is nitrogen, the treatment time is 2 min, the treatment pressure is 100 Pa, the treatment temperature is 60° C., and the treatment power is 100 W) to obtain active high-performance fibers;
[0047] S32, preparing core-shell Si3N4@ZIF-8 dispersion: 62.94g of nano-Si3N4, 141.18g of 2-methylimidazole, and 51.03g of zinc nitrate were dissolved in 1000mL of ethanol, and a core-shell Si3N4@ZIF-8 dispersion was prepared by a microwave-ultrasound-assisted method (treatment time 10h, temperature 140°C);
[0048] S33, preparation of Si3N4@ZIF-8 modified fiber: immerse the active high-performance fiber obtained in S31 in the core-shell Si3N4@ZIF-8 dispersion obtained in S32, anchor the core-shell Si3N4@ZIF-8 crystals on the surface of the active high-performance fiber by chemical deposition method (treatment temperature 80°C, treatment time 4h), to prepare Si3N4@ZIF-8 modified fiber;
[0049] S34, preparing a high-performance fiber composite material: taking thermoplastic polyurethane and dissolving it in dimethylformamide to prepare a solution with a concentration of 13 wt%, immersing the Si3N4@ZIF-8 modified fiber obtained in S33 into the above mixed solution for interface modification (treatment time 1 h) to prepare a high-performance ultra-high molecular weight polyethylene fiber composite material;
[0050] S35. Preparation of high-strength, corrosion-resistant and puncture-resistant fiber composite materials: Take two layers of the high-performance ultra-high molecular weight polyethylene fiber composite material obtained in S34 and stack them to prepare a high-strength, corrosion-resistant and puncture-resistant fiber composite material.
[0051] Comparative Example 1 (without anchoring the core-shell Si3N4@ZIF-8 crystal on the surface of the active high-performance fiber, directly using the polymer / polymer coating solution to modify the interface of the plasma-treated active high-performance fiber)
[0052] The only difference from Example 1 is that the core-shell Si3N4@ZIF-8 crystals are not anchored on the surface of the active high-performance fiber. Specifically, the active high-performance aramid fiber is prepared by the same preparation method as in Example 1, and then PET (10 g / m 2 ) The surface of the active high-performance aramid fiber was subjected to interface modification by hot pressing with a flat hot press (the hot pressing temperature was 200°C, the hot pressing pressure was 5 MPa, and the hot pressing time was 5 min) to prepare a high-performance aramid fiber composite material. Finally, two layers of the obtained high-performance aramid fiber composite material were stacked and composited to prepare a flame-retardant, high-strength, corrosion-resistant, and puncture-resistant fiber composite material.
[0053] Comparative Example 2 (no plasma treatment of high performance fibers)
[0054] The only difference from Example 1 is that this embodiment does not perform plasma treatment on the high-performance fibers.
[0055] Comparative Example 3 (Interface modification of Si3N4@ZIF-8 modified fibers without using polymer / polymer coating solution)
[0056] The only difference from Example 1 is that this example does not use PET polymer coating solution to perform interface modification on Si3N4@ZIF-8 modified fibers.
[0057] Comparative Example 4 (No Lamination of High-Performance Fiber Composite Materials)
[0058] The only difference from Example 1 is that this example does not perform two-layer lamination on the obtained high-performance fiber composite material.
[0059] Structural characterization and performance testing
[0060] Scanning electron microscope observation: The microstructure of the modified high performance fibers was observed by field emission scanning electron microscope (model JSM-7900F, JEOL).
[0061] Chemical stability test : According to EN:374 standard, chemical stability test was carried out to determine the resistance of samples to strong acid (H2SO4, 98%) and alkali (NaOH, 40%). The fabric was immersed in a strong acid / alkali solution with a pH range of 1-14 for 120 hours, and the weight loss rate of the composite material was determined.
[0062] Puncture resistance performance test: The puncture test is carried out using a puncture resistance performance tester (Hongda). The test standard is based on ASTM F1342-05. Each parameter sample is tested 6-8 times, and the results are taken as the average value.
[0063] Mechanical properties test: The obtained lightweight, high-strength, heat-resistant and stab-resistant fiber composite material was cut to obtain tensile specimens, and the mechanical properties of the composite material were tested using a universal testing machine (model 5982, Instron, USA) according to the ASTM D638-2003 plastic tensile properties test standard of the American Society for Testing and Materials. At least 3 parallel test samples were guaranteed for each group, and the results were averaged.
[0064] Table 1. Corrosion resistance test results of high-strength corrosion-resistant and puncture-resistant fiber composite materials obtained in Examples and Comparative Examples
[0065]
[0066] Table 2. Puncture resistance and mechanical properties of high-strength corrosion-resistant and puncture-resistant fiber composite materials obtained in Examples and Comparative Examples
[0067]
[0068] Experimental results: Figure 2 It shows that a dense layer of core-shell Si3N4@ZIF-8 nanocrystals is evenly distributed on the surface of the aramid fiber obtained in Example 1. Figure 3In the experiment, a dense layer of core-shell Si3N4@ZIF-8 nanocrystals was evenly distributed on the surface of the modified ultra-high molecular weight polyethylene fiber. Among them, plasma treatment is mainly used to change the chemical composition and structure of the fiber surface, increase surface functional groups (such as hydroxyl and carboxyl groups), and thus improve the ability to combine with other materials (such as coatings, adhesives and dyes). Therefore, the active fiber after plasma treatment shows good combination with the core-shell Si3N4@ZIF-8 nanocrystals.
[0069] It can be seen from Table 1 that compared with Comparative Examples 1-3, the obtained Examples 1-3 all have strong resistance to chemical substances. The maximum weight loss rate of Examples 1-3 after 120 hours in strong acid / alkali solution is only 5%. This is mainly due to the polymer / polymer coating solution on the fiber surface, which mainly acts as a physical barrier to protect high-performance fibers from direct contact with harmful chemicals, thereby reducing the risk of corrosion and degradation. At the same time, polymers such as PVC and PET have good chemical stability and corrosion resistance and can resist erosion by a variety of chemical media. This property can effectively extend the service life of the composite material, so the modified fiber composite material has good corrosion resistance. In sharp contrast, Comparative Example 3 does not use polymer / polymer coating solution to perform interface modification on the core-shell Si3N4@ZIF-8 modified fiber, and its weight loss rate reaches 57%.
[0070] Table 2 shows the puncture resistance and mechanical properties of the high-strength corrosion-resistant and puncture-resistant fiber composite materials obtained in the examples and comparative examples. In Example 1, the puncture force and tensile strength of the laminated composite material reached 550N and 820MPa, respectively. The improvement in mechanical properties is mainly due to the core-shell Si3N4@ZIF-8 nanocrystals deposited on the fiber surface, which can effectively bond with the fiber surface to produce interfacial interactions, forming a nano-scale particle-fiber matrix interface, thereby enhancing the toughness and stiffness of the fabric, allowing more fibers to participate in movement and deformation during the puncture process, thereby increasing the ability to absorb and disperse energy. In contrast, the maximum puncture force of the two layers in the comparative example is only 265N.
[0071] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can easily think of changes or replacements within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims. It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further explain various possible combinations. In addition, the various different embodiments of the present invention can also be combined arbitrarily, as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a high-strength, corrosion-resistant and puncture-resistant fiber composite material, characterized in that: The following steps are involved: S1. Preparation of active high-performance fibers: cleaning and drying the surface of the high-performance fibers, and then placing the fibers in a plasma reaction chamber for plasma treatment, thereby obtaining active high-performance fibers; S2, preparing core-shell Si3N4@ZIF-8 dispersion: dissolving nano-Si3N4, zinc salt and 2-methylimidazole in a sufficient amount of alcohol solvent, and preparing core-shell Si3N4@ZIF-8 crystal dispersion by microwave-ultrasound assisted method; S3, preparation of Si3N4@ZIF-8 modified fibers: anchoring the core-shell Si3N4@ZIF-8 crystals on the surface of the active high-performance fiber obtained in S1 by using the core-shell Si3N4@ZIF-8 dispersion obtained in S2 through a surface deposition process to obtain Si3N4@ZIF-8 modified fibers; S4, preparation of high-performance fiber composite materials: using polymer / polymer coating solution to perform interface modification on the Si3N4@ZIF-8 modified fiber obtained in S3 to prepare high-performance fiber composite materials; S5. Preparation of high-strength, corrosion-resistant and puncture-resistant fiber composite materials: The high-performance fiber composite materials obtained in S4 are laminated and compounded to finally prepare high-strength, corrosion-resistant and puncture-resistant fiber composite materials.
2. The method for preparing a high-strength, corrosion-resistant and puncture-resistant fiber composite material according to claim 1, characterized in that: In the step S1, the gas used in the plasma treatment is at least one of oxygen, nitrogen, hydrogen, argon and helium, the treatment time is 0.5-10 min, the treatment pressure is 10-130 Pa, the treatment temperature is 20-60° C., and the treatment power is 20-300 W.
3. The method for preparing a high-strength, corrosion-resistant and puncture-resistant fiber composite material according to claim 1, characterized in that: The high-performance fiber in step S1 is at least one of ultra-high molecular weight polyethylene fiber, aramid fiber, polysulfone fiber, nylon fiber, carbon fiber, polyimide fiber, and polyester fiber.
4. The method for preparing a high-strength, corrosion-resistant and puncture-resistant fiber composite material according to claim 1, characterized in that: The zinc salt in step S2 is at least one of zinc acetate, zinc chloride, zinc nitrate, zinc sulfate, zinc acetate, zinc phosphate, and zinc carbonate. The concentration of the zinc salt solution is 0.01-0.5 mol / L. The treatment time of the microwave-ultrasound-assisted method is 1-48 h, and the treatment temperature is 20-200° C. The mass ratio of nano-Si3N4, 2-methylimidazole, and zinc salt in the core-shell Si3N4@ZIF-8 dispersion is 1:2-3:0.7-0.
9.
5. The method for preparing a high-strength, corrosion-resistant and puncture-resistant fiber composite material according to claim 1, characterized in that: In the step S2, the alcohol solvent is at least one of methanol, ethanol, benzyl alcohol, ethylene glycol, propylene glycol, n-butanol, and cyclohexanehexol, and the average particle size of the core-shell Si3N4@ZIF-8 crystal is 3.0 μm to 4.0 μm.
6. The method for preparing a high-strength, corrosion-resistant and puncture-resistant fiber composite material according to claim 1, characterized in that: The surface deposition process in step S3 is at least one of an ultrasonic assisted method, a heat treatment method (solvent evaporation, heating crystallization, etc.), a covalent bonding method, a chemical deposition method, and an electrochemical deposition method.
7. The method for preparing a high-strength, corrosion-resistant and puncture-resistant fiber composite material according to claim 1, characterized in that: The polymer in step S4 is at least one of polyethylene terephthalate, polyurethane, polyvinyl chloride, polypropylene, polyethylene, polycarbonate, polyamide, polyester elastomer, polyetheretherketone, ethylene-vinyl acetate copolymer, polyvinylidene fluoride, and polytetrafluoroethylene.
8. The method for preparing a high-strength, corrosion-resistant and puncture-resistant fiber composite material according to claim 1, characterized in that: The polymer coating solution in step S4 is a mixture of a polymer and an organic / inorganic solvent or a mixed coating solution formed by a resin and an inorganic powder; The interface modification process in step S4 is one or more of hot pressing, dipping, coating, spraying, roller coating, roller pressing, casting, and ultrasonic vibration treatment.
9. The method for preparing a high-strength, corrosion-resistant and puncture-resistant fiber composite material according to claim 1, characterized in that: In step S5, the number of laminated layers is 2 to 40, wherein the limiting oxygen index of two layers is 20-45%, the maximum puncture force is 350-550N, and the tensile strength is 450-820MPa.
10. A high-strength, corrosion-resistant and puncture-resistant fiber composite material obtained by the preparation method according to any one of claims 1 to 9 and use thereof.
Citation Information
Patent Citations
Multi-scale carbon fiber, reinforced toughened epoxy composite and their preparation methods
CN110714330A
Carbon nanomaterial modified ultra-high molecular weight polyethylene fiber and preparation method thereof
CN111705501A
Preparation method of ZIF-8 modified high-temperature-resistant composite nanofiber membrane
CN118650945A